Biochemistry Laboratory Manual For Undergraduates. - Fernandez, Timea Gerczei (De Gruyter, 2015)
Biochemistry Laboratory Manual for undergraduates is the first textbook on the market that uses a highly relevant model, antibiotic resistance, to teach seminal topics of biochemistry and molecular biology. Inclusion of a research project does not entail a limitation: this manual includes all classic biochemistry techniques such as HPLC or enzyme kinetics and is complete with numerous problem sets relating to each topic.